The impact of accounting ethics on the quality of financial reports at Ajdabiya University (Comprehensive Journal of Science, 2026)
This study aims to examine the impact of accounting ethics on the quality of financial reporting from the perspective of employees working in the Financial Administration at the University of Ajdabiya. A comprehensive survey was conducted covering the entire study population, which included all employees within the financial administration, such as accountants, auditors, managers, and department heads. A structured questionnaire was designed and distributed to all members of the study population. The findings revealed that accounting ethics among employees at the University of Ajdabiya have a positive impact on the quality of financial reporting. The results also indicated a high level of professional competence, confidentiality of accounting information, objectivity, integrity, and professional behavior among the accounting staff within the financial administration. Furthermore, the study confirmed that professional ethics are reflected in and significantly influence the quality of financial reports. Accordingly, the study recommends the organization of specialized workshops focused on professional ethics to further enhance ethical awareness and practices within the accounting field.
Keywords: Accounting Ethics – Financial Reporting Quality – Professional Integrity – Professional Competence